BLENDED LEARNING IN TEACHING ENGLISH TO UNIVERSITY STUDENTS - Qabas Jameel Rashid; Inas Hisham Abdul- Abbas; Majid Rasim Younus (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Fast technological advances of the modern world should be used for educational purposes. Blended learning gives an opportunity to make a shift from traditional methods to more innovative ones with the use of technology, which encourages both teaching and learning, provides flexibility in education. However, there are still many problems that need to be solved in order to raise the effectiveness of blended learning. The article considers the prospects and challenges of using blended learning in teaching English to university students, analyses possible solutions, determines the requirements to online English language teaching course and grounds the stages of its development.